2021
DOI: 10.1002/aenm.202100332
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering for Expediting Li–S Chemistry: Strategies, Mechanisms, and Perspectives

Abstract: as well as the cost-effectiveness and environmental-friendliness of sulfur resource. [1][2][3][4][5][6][7][8] However, a suite of troublesome problems, mainly pertaining to sluggish redox kinetics and severe polysulfide (PS) shuttle, has hampered the pathway for pursuing Li-S commercialization. [9][10][11][12][13] For one thing, the conversion from PS to Li 2 S exhibits large energy barriers, which is regarded as the rate-determining step of sulfur reduction reaction (SRR) process. For another, Li 2 S is prone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
153
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(153 citation statements)
references
References 181 publications
(218 reference statements)
0
153
0
Order By: Relevance
“…[15,16] Defect engineering (e.g., O-, S-, Se-deficient) can significantly increase catalyst conductivity, supply active sites, improve polysulfide confinement, and increase catalytic activity. [17][18][19][20][21][22][23][24] For example, Chen et al reported selenide defects in a Sb 2 Se 3−x microsphere that exhibited high-conductivity and stable sulfur electrochemistry. [19] Metal-telluride dichalcogenides exhibit metallic properties with high conductivity (e.g., 1.15 × 10 6 S m −1 for NiTe 2 ), relative to sulfide and selenide counterparts (0.55 S m −1 for NiS 2 , 10 S m −1 for NiSe 2 ), and exhibit high electrocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Defect engineering (e.g., O-, S-, Se-deficient) can significantly increase catalyst conductivity, supply active sites, improve polysulfide confinement, and increase catalytic activity. [17][18][19][20][21][22][23][24] For example, Chen et al reported selenide defects in a Sb 2 Se 3−x microsphere that exhibited high-conductivity and stable sulfur electrochemistry. [19] Metal-telluride dichalcogenides exhibit metallic properties with high conductivity (e.g., 1.15 × 10 6 S m −1 for NiTe 2 ), relative to sulfide and selenide counterparts (0.55 S m −1 for NiS 2 , 10 S m −1 for NiSe 2 ), and exhibit high electrocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows CeÀ TiO 2 maintains distinguished catalysis at high temperatures, [16] so the catalysis of 0.4 CeÀ TiO 2 for polysulfides at elevated temperatures is investigated by the symmetric cells of Li 2 S 6 as Figure S14 shows. For all temperatures, the CV curves of the cells without Li 2 S 6 exhibit capacitive behavior, however, the ones with Li 2 S 6 exhibit a much higher current density, manifesting the 0.4 CeÀ TiO 2 /rGO and TiO 2 /rGO can provide effective catalysis for Li 2 S 6 at elevated temperatures.…”
Section: Electrochemical Performance At Elevated Temperaturesmentioning
confidence: 99%
“…[15] Research also had proved that cation doping in TiO 2À x can improve the adsorption and catalytic activity for polysulfides. [16] Herein, we fabricated the anatase TiO 2 doping by Ce element (Ce-doped TiO 2 ) to induce oxygen vacancies, [17] increasing the catalytic activity of TiO 2 . [18,19] The Ce-doped TiO 2 was served as a strong absorbent and catalyst, and the reduced graphene oxide (rGO) was combined to provide a conductive network and a high specific area for hosting sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…However, the commercial application of Li-S batteries is still constrained by many challenges. The inevitable dissolution of lithium polysulfides (LiPSs) intermediates in the electrolytes and the shuttling of LiPSs between the cathode and anode result in low sulfur utilization, swift capacity degradation and the corrosion of lithium anode [9][10][11][12][13][14][15][16]. In addition, the sluggish redox kinetics resulting from insulating sulfur and Li 2 S during discharge/charge cycles limits the efficient conversion of sulfur species, impairing the rate performance and cycling stability of Li-S batteries [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%